GAMBARAN PERILAKU PENDERITA TB PARU DALAM PENCEGAHAN PENULARAN TB PARU DI KABUPATEN KLATEN - Hertian Ilham Hutama; Emmy Riyanti; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Disease of pulmonary tuberculosis in klaten regency has increased from year 2014- 2017. Efforts to the prevention of disease pulmonary tuberculosis is an important thing to reduce the rate of death caused by disease pulmonary tuberculosis. This Research aims to understand the description about the behavior of TB patients pulmonary in prevent transmission of pulmonary tuberculosis in Klaten regency. The kind of research used is descriptive with the approach cross-sectional study. The population is a whole tb patients lungs in 3 working areas of public health service in klaten regency. The sample of the 50 respondents tb patients pulmonary a total of sampling in accordance with set criteria. Data analysis using analysis univariat the research results show characteristics of respondents pulmonary tuberculosis 26 % was 46-55 years, 70 % men, 46 % senior high school education, 34 % work laborers, 94 % income less than Rp 1.660.000. Variable knowledge 62% good , 66 % good attitude , the availability of medicines 76 % available , accessibility of to health facilities 56 % difficult , the facilities and infrastructures 66 % enough. Variable family encouragement, support health workers, and support friend each of 54 % good. Behavior variable prevent transmission of pulmonary tuberculosis 62 % good.